2018
DOI: 10.3390/nu10091324
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Consumption in Spain: Patterns, Nutrient Intake and Quality. Findings from the ANIBES Study, a Study from the International Breakfast Research Initiative

Abstract: This study aimed to investigate energy, nutrient and food group intakes at breakfast in Spain and to examine for the first time, their relationship to the overall Diet Quality (DQ). The data used were from the Spanish ANIBES (anthropometric data, macronutrients and micronutrients intake, practice of physical activity, socioeconomic data and lifestyles in Spain), a cross-sectional study using a nationally representative sample of the Spanish population (9–75 years old). DQ was assessed using the Nutrient Rich F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
56
5
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 30 publications
17
56
5
2
Order By: Relevance
“…We found that the majority of participants (97% for whole sample) reported breakfast consumption on the dietary recording day. The figure is somewhat higher than those observed in other countries based on one-day dietary data, such as in the US (83% for children and 85% for adults) [ 6 ], Canada (overall 90%) [ 2 ], and Australia (91% for children) [ 7 ]. Our finding that the prevalence of breakfast skippers was high in young adults (7.7%) compared with other age groups (0.7–2.6%) might reflect their busy lifestyles (particularly working men).…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…We found that the majority of participants (97% for whole sample) reported breakfast consumption on the dietary recording day. The figure is somewhat higher than those observed in other countries based on one-day dietary data, such as in the US (83% for children and 85% for adults) [ 6 ], Canada (overall 90%) [ 2 ], and Australia (91% for children) [ 7 ]. Our finding that the prevalence of breakfast skippers was high in young adults (7.7%) compared with other age groups (0.7–2.6%) might reflect their busy lifestyles (particularly working men).…”
Section: Discussionmentioning
confidence: 60%
“…The number of individual participants in the dietary survey part of NHNSJ 2012 was 32,228. Consistent with the IBRI project [ 2 , 3 , 4 , 5 , 6 , 7 ], we excluded data from individuals aged ≤ 5 years ( n = 1370); lactating or pregnant women ( n = 368), because they were presumed to be not following their usual diet; and individuals with missing information on the variables of interest ( n = 8038, mainly body height or weight). The final analysis sample consisted of 22,452 individuals, who were divided into four age groups for analysis: children (aged 6–11 years; n = 1444), adolescents (aged 12–17 years; n = 1134), younger adults (aged 18–49 years; n = 6531), and older adults (aged ≥ 50 years; n = 13,343).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations